Radiographic retropharyngeal lymph node involvement in HPV‐associated oropharyngeal carcinoma: Patterns of involvement and impact on patient outcomes. Issue 9 (8th January 2019) - Lin, Timothy A.; Garden, Adam S.; Elhalawani, Hesham; Elgohari, Baher; Jethanandani, Amit; Ng, Sweet P.; Mohamed, Abdallah S.; Frank, Steven J.; Glisson, Bonnie S.; Debnam, J. Matthew; Sturgis, Erich M.; Phan, Jack; et al.
Abstract : Background: The objective of the current study was to characterize the incidence, pattern, and impact on oncologic outcomes of retropharyngeal lymph node (RPLN) involvement in HPV‐associated oropharyngeal cancer (OPC). Methods: Data regarding patients with HPV‐associated OPC who were treated at The University of Texas MD Anderson Cancer Center with intensity‐modulated radiotherapy from 2004 through 2013 were analyzed retrospectively. RPLN status was determined by reviewing pretreatment imaging and/or reports. Outcomes analysis was restricted to patients with lymph node‐positive (+) disease. Kaplan‐Meier survival estimates were generated and survival curves were compared using the log‐rank test. Bayesian information criterion assessed model performance changes with the addition of RPLN status to current American Joint Committee on Cancer staging. Competing risk analysis compared modes of disease recurrence. Results: The incidence of radiographic RPLN involvement was 9% (73 of 796 patients) and was found to vary by primary tumor site. The 5‐year rates of freedom from distant metastases (FDM) and overall survival were lower in patients with RPLN(+) status compared with those with RPLN‐negative (‐) status (84% vs 93% [ P  = .0327] and 74% vs 87% [ P  = .0078], respectively). RPLN(+) status was not found to be associated with outcomes on multivariate analysis. Bayesian information criterion analysis demonstrated that current American Joint Committee on Cancer staging was not improved with the inclusion of RPLN. Locoregional and distant disease recurrence probabilities for those patients with RPLN(+) status were 8% and 13%, respectively, compared with 10% and 6%, respectively, for those with RPLN(‐) status. RPLN(+) status portended worse 5‐year FDM in the low‐risk subgroup (smoking history of <10 pack‐years) and among patients who received concurrent chemotherapy but not induction chemotherapy. Conclusions: RPLN(+) status was associated with worse overall survival and FDM on univariate but not multivariate analysis. In subgroup analyses, RPLN(+) status was associated with poorer FDM in both patients with a smoking history of <10 pack‐years and those who received concurrent chemotherapy, suggesting that RPLN(+) status could be considered an exclusion criteria in treatment deintensification efforts seeking to omit chemotherapy. Abstract : The incidence of radiographic retropharyngeal lymph node (RPLN) involvement in patients with HPV‐associated oropharyngeal cancer is 13% for those with primary tumors of the palatine tonsil and 5% for patients with primary tumors of the base of the tongue. Despite these patients receiving more intensive therapy, RPLN involvement appears to correlate with poorer 5‐year freedom from distant metastases and overall survival rates (univariate analysis) and demonstrates a differential in terms of patterns of failure, but these differences in outcome are not maintained on multivariate analysis. However, the patterns of failure and subgroup analyses suggest that RPLN involvement could be considered another marker of regionally advanced disease with a resultant elevated risk of distant disease recurrence and be considered an exclusion criteria for treatment deintensification.